Comparison of the enrollment percentages of magnet and non-magnet schools in a large urban school district. - Arcia, Emily (Education Policy Analysis Archives, 2006)
Are magnet schools in a position to meet diversity ideals? As districts are declared unitary and released from court ordered desegregation, many are framing their commitments to fairness and equity in terms of diversity˜i.e., comparable rates of participation and comparable educational outcomes in all segments the student population. In this study, the enrollment statistics for magnet and contiguous non-magnet public schools in Miami-Dade County Public Schools, a large, urban district that had been released from court ordered desegregation, were compared to each other and to district enrollment averages at two time points: the year the district was declared unitary and four years hence. Findings indicated that within four years of being declared unitary, the gains that the magnet schools had made with regards to Black/non-Black desegregation had eroded substantially. Also, in the four year span, magnet schools had not made significant strides in meeting the diversity ideals adopted by the district at being released from supervision by the court. These findings highlight the difficulty of attaining diversity in student enrollment characteristics when quotas are not used and suggest that recruitment and enrollment policies must be crafted with care if districts are to achieve diversity goals.